Real Earnings Management: Evidence From Vietnam - Nguyen, Thu Hang; Nguyen, Manh Hiep (Journal of International Economics and Management, 2016)
We examine real earnings management in Vietnamese listed firms. In accordance with prior literature, we find that real earnings management is more severe in firms that have low ROA, low market-to-book ratio. Moreover, firms that have earnings close to zero are more likely to engage in real earnings management. This conclusion is consistent across different proxies used. Specifically, these firms exhibit significantly lower abnormal cash flows, lower discretionary expenses but higher productions costs than other firms do. Based on the results, we conjecture that reduction of discretionary expenses and overproduction may be more favorable tactics in real earnings managment.